(untitled) (Research, Society and Development, 2022)
Percutaneous Endoscopic Gastrostomy (PEG) is a method that has been widely used as an alternative feeding method for patients who have impaired mastication and swallowing. The study aimed to verify whether the application of waterproof adhesive dressing is effective in preventing water infiltration at the site of the GEP feeding stoma in the therapeutic pool, simulating a real aquatic rehabilitation situation. This is a cross-sectional study in which cotton samples that were inside the dressing were tested and were compared in two weighings after the participant entered the therapeutic pool, the first weighing performed immediately after passive and active immersion and the second weighing after a period of drying in the oven. Ninety procedures were performed, with the participation of 45 healthy volunteers of both sexes, aged between 18 and 60 years. The weighing values ​​were statistically significant for the confirmation of water infiltration inside the dressing in 1/5 of the cases, with the participants in the active modality having the highest proportion of infiltration. When performing the analysis for BMI and presence of hair in the abdominal region, there was no statistically significant difference between the results previously obtained. The occlusive dressing is effective to prevent water infiltration during patient immersion in the therapeutic pool in 80% of cases.